Optimalisasi Peran Kantor Urusan Agama dalam Pelayanan Keagamaan dan Pembinaan Masyarakat di Kecamatan Medan Tembung - Husna Sari Siregar; Fitra Dana Hasibuan; Muhammad Zakaria; Amanda Putri Lubis; Muhammad Iqbal Fahreza Rambe (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The Office of Religious Affairs (KUA) plays a crucial role in the development and fostering of community life. Therefore, it is a unit within the Ministry of Religious Affairs, located in various regions, and directly interacts with the wider community. Islamic law requires a marriage contract (Ijab Qabul), a verbal declaration of the relationship between the bride and groom. The conclusion is that the religious services implemented have been running well. This is evident from several services implemented. The collaboration between KUA officials, counselors, and community leaders has been supported by the latest service program, the KUA Revitalization, a significant breakthrough program implemented by the Indonesian Ministry of Religious Affairs.